Perbandingan Kualitas Air Mata Antara Pengguna Dan Non Pengguna Lensa Kontak - Arief Witjaksono; Ranie Khairunnisa (Sehat MasadaJurnal, 2020)
The use of contact lenses can cause dry eyes, it is caused by mechanical irritation of the meibomian gland. The meibomian gland produces a layer of fat which functions to inhibit evaporation of the tear layer. Disruption of the function of the meibomian gland causes the tear layer to evaporate quickly. Contact lenses also reduce the sensitivity of the eye surface so that the tear layer production reflex decreases. Increased evaporation accompanied by a decrease in tear production causes most contact lens users to experience dry eyes. The purpose of this study is to find out the difference in the quality of tears between users and non-contact lens users. Case control design with observational techniques has been conducted. This study used a schirmer test and observational sheet. The results of the study showed that of the 20 active contact lens users 14 (70.0%) had dry eyes and 3 (15.0%) of 20 non-contact lens users had dry eyes. Statistically Independent T-Test r = 0.00 <0.005 there is a difference between the quantity of tears of users and non contact lens users. It is recommended to pay attention to the use of contact lenses for long usage, usage period and lubricant on contact lenses so as not to cause complications in the use of contact lenses and dry eyes.